Time–Motion Analysis of the 2023 Women’s World Boxing Championships Finals - Francesca Martusciello; Andrea Perazzetti; Arben Kaçurri; Marco Consolati; Antonio Tessitore (Sports)
Background: This study investigated boxers’ activity profiles during the final matches (3 × 3 min format) of the IBA 2023 Women’s World Boxing Championships. Methods: Footage of the 12 finals was used to analyse the frequency and duration of fighting (F), punching (P), clinching (C), no-fighting (NF), and arbitral interruption (AI) phases. The analysis was conducted both for weight categories and divisions (lightweight (LWC): 48, 50, 52, 54, 57, and 60 kg; middleweight (MWC): 63, 66, 70, and 75 kg; heavyweight (HWC): 81 and 81+ kg). Results: Pooled data per round revealed significant differences for P (<0.001), C (p = 0.002), NF (p < 0.001), and AI (p < 0.001) phases, as well for P mean duration across rounds (p < 0.001). The MWC division showed significantly shorter F duration compared with the LWC (p = 0.007) and MWC divisions (<0.001). The F/NF total time ratio showed a prevalence of F in the 48, 50, 63, and 81+ kg categories, while NF prevailed in the 54, 57, 60, and 75 kg categories. Conclusions: While HWC primarily relied on C actions, the 54, 57, 60, and 75 kg categories showed higher NF frequency. This fact explains a different strategic match management approach with deliberate rhythm, controlled pauses, and opponent analysis, which coaches should consider for enhancing athletes’ performance by considering weight categories.